Digital Literacy in The Family (Case Study of Restricting Youtube Use in Children) - Anisa, Anisa Rahmawati (Jogjakarta Communication Conference (JCC), 2025)
The rapid advancement of digital technology has transformed media consumption patterns within families, particularly among children. YouTube, as one of the most widely accessed video platforms for children, offers a vast array of educational content. However, it also presents risks such as digital addiction, exposure to inappropriate content, and potential disruptions to children's social and emotional development. Therefore, this study aims to analyze how parents manage their children's YouTube usage through parental mediation strategies to optimize its role as a learning tool. This research employs a qualitative descriptive method with a case study approach, gathering data through in-depth interviews with three families whose children, aged 6–12 years, actively use YouTube. The findings reveal that parents implement three primary parental mediation strategies: active mediation (open discussions about the content children consume), restrictive mediation (strict regulations on screen time and content access), and co-use mediation (direct parental supervision to ensure content safety). The study further indicates that each family adopts different communication patterns influenced by parental availability, children's level of openness, and the effectiveness of imposed regulations. Parents who consistently engage in active mediation foster children's critical awareness, enabling them to independently select educational content. Meanwhile, restrictive mediation, when applied consistently, effectively limits screen time but often faces resistance from children, who tend to negotiate for extended viewing time. Co-use mediation proves to be the most effective approach for controlling content quality, yet it requires a high level of parental involvement, which is often constrained by time constraints. Moreover, the study identifies several challenges in implementing parental mediation, including limited parental availability for supervision, difficulties in maintaining rule consistency, and children's emotional resistance to YouTube restrictions. However, the findings suggest that with open communication, active parental engagement, and consistent enforcement of rules, parents can cultivate healthy media consumption habits among children. Consequently, this study underscores the crucial role of digital literacy within families in balancing the educational benefits of YouTube while mitigating its potential negative impacts in the digital era.